2020
DOI: 10.3390/agronomy10101574
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Biofortification of Vegetables Could Improve Iodine Supplementation Status

Abstract: Iodine is an essential trace element for both humans and animals. It is essential to produce important hormones by the thyroid gland. In most inland areas, the soils are iodine deficient and its amount is insufficient to produce agricultural crops with adequate iodine content to cover the recommended daily intake. In connection with the occurrence of iodine deficiency disorders (IDDs), it has been the subject of intensive research in the past. However, following the introduction of iodized table salt in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 66 publications
1
12
0
2
Order By: Relevance
“…Though neither Se nor I are essential to most known plants, they are vital for several sea microalgae species [ 10 ]. Although I compounds are transferred with aerosols to remarkable distances from the seashore, the inland regions in the world always suffer from lack of I causing global problems of I deficiency [ 11 ], which along with the wide distribution of Se-deficient soils, results in serious ecological risks.…”
Section: Consumption Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though neither Se nor I are essential to most known plants, they are vital for several sea microalgae species [ 10 ]. Although I compounds are transferred with aerosols to remarkable distances from the seashore, the inland regions in the world always suffer from lack of I causing global problems of I deficiency [ 11 ], which along with the wide distribution of Se-deficient soils, results in serious ecological risks.…”
Section: Consumption Levelsmentioning
confidence: 99%
“…In general, Se content in most agricultural crops, known to be non-accumulators of Se, may be increased up to 0.2–3000 mg kg −1 d.w. without growth inhibition, depending on the Se form and dose [ 12 ], as it also happens for I supplementation [ 11 ]. Considering the 80–90% water content in most vegetables and the daily Se and I requirements ( Table 2 ), such biofortification values are capable to fulfill up to 100% of the Se and I adequate consumption levels.…”
Section: Consumption Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine is traditionally not considered an essential element for higher plants, even if very recent studies have indicated its involvement in plant metabolism as a micronutrient 32 . Although several experiments showed how high concentrations of this element can be toxic for plants 8 , 33 , at low concentrations iodine can act as a growth enhancer, positively influencing growth and nutritional parameters 33 36 . It was also hypothesized that, by inducing an antioxidant response, low levels of iodine may protect plants from both biotic and abiotic stress conditions, such as salinity or heavy metals 8 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It was also hypothesized that, by inducing an antioxidant response, low levels of iodine may protect plants from both biotic and abiotic stress conditions, such as salinity or heavy metals 8 , 37 . The impact of iodine on vegetables strongly depends on the species, the iodine form, the application method, and the properties of the substrate where plants are grown 36 , 37 . It is, however, undoubted that plants are able to take up iodine from the soil through the root system and from the air through the leaves, and that the quantity taken up is usually dependent on the amount of iodine available in the environment 8 , 37 .…”
Section: Discussionmentioning
confidence: 99%